(untitled) (Journal of Bangladesh Institute of Planners, 2020)
Maritime region was a pertaining issue for its existing source of energy and resources and it was envisaged as an economic hub for a developing country like Bangladesh. Be a distinction nation, there was a notion to attain sufficiency and environmental sustainability by the proper utilization of maritime resources, but it was far behind for several reasons specially lack strategy and planning. IFAS and EFAS analysis manifested an object’s current situation and made it possible to aggravate future action plans. The objective of the study was to analyze 32 indicators of maritime region through internal factor analysis system (IFAS) and external factor analysis system (EFAS) where the indicators of strength and weakness were conceived in IFAS and opportunity and threat were enumerated in EFAS. The primary data were collected through questionnaire survey and deep interview and secondary data were excerpted from different published reports, research paper and article etc. and organized by IFAS and EFAS matrix. Based on the score of IFAS and EFAS the results showed that the position of maritime region was in quadrant 3 (internal weakness, IFAS≤2 and external threat, EFAS≤2) and highest score was 3.733 (IFAS). Considering quadrant 3, the aftermath suggested some strategical approaches for achieving sustainable development and underpinning economic growth in Bangladesh. JBIP, Vol. 13, 2020 (Printed in June 2021), pp. 29-45